REPETITION AND RESTITUTION: TRANSLATING PAUL CELAN - Felstiner, John (Holocaust and genocide studies, 1990)
The poems of Paul Celan (1920–1970), being written in his German mother tongue that turned abruptly into his mother's murderers' tongue, form an acute testimony to the European Jewish catastrophe. Manifold instances of repeti–tion build into the poems literal enactments of a contradictory, nullifying expen-ence, but repetition also generates an ongoing, future-bent movement. By tracing closely the process of translating a Celan lync, this essay attempts to show how even that process of repetition may bear out the restitutive impulse of the poem itself.